Enhancing Student Engagement and Learning Outcomes through the Implementation of Flipped Classroom Pedagogy in Higher Education (Journal of Interdisciplinary Insights, 2024)
This study examines the implementation and effectiveness of the flipped classroom pedagogy in education-focused programs. Using a mixed-methods approach, the researchers investigated student perceptions, the relationship between the flipped classroom, student engagement, and learning outcomes, as well as the challenges and barriers encountered by students. The results indicate overall positive perceptions of the flipped classroom approach, with strong positive correlations between the flipped classroom, student engagement, and learning outcomes. However, the study also identified potential challenges, particularly regarding increased workload and self-directed learning requirements. The findings highlight the critical role of student engagement in maximizing the benefits of the flipped classroom and suggest that targeted support measures and contextual considerations are important for successful implementation. The study provides valuable insights and recommendations for institutions seeking to adopt and enhance the flipped classroom approach in education-focused programs.